Modernisation of Railway Junctions - Malicek, Ivan (Communications - Scientific letters of the University of Zilina, 1999)
Modernisation of railway transport is not possible without complex modernisation of railway stations and junctions. This modernisation will actually mean their preparation for implementation of the main tasks of railway for the future. The paper presents some of the most necessary arrangements, without which the railway will not be able to compete with other modes of transport.